"Dancing As Gracefully As I Can": A Developmental Model Of Coping Strategies In Successfully Adapting To Hiv Infection - Patricia M. Reeves; Sharan B. Merriam; Bradley C. Courteany (Adult Education Research Conference, 1998)
The purpose of this study was to understand the use of coping strategies in successfully adapting to HIV infection. Data analyzed from 18 interviews revealed that coping strategies employed immediately after diagnosis differed from those used later. An underlying developmental process in the use of coping strategies was also uncovered.